Characteristics of Endophthalmitis after Cataract Surgery in the United States Medicare Population - Gower, Emily W. (Ophthalmology, 2015)
PURPOSE: Endophthalmitis is a rare but sight-threatening infection after cataract surgery. Roughly one third of eyes remain blind after treatment. We report United States population-based data on microbiological investigations and treatment patterns plus risk factors for poor outcomes. DESIGN: Retrospective cohort study. PARTICIPANTS: Medicare beneficiaries from 5 states in whom endophthalmitis developed within 6 weeks after cataract surgery in 2003 and 2004. METHODS: We identified endophthalmitis cases occurring after cataract surgery using Medicare billing claims. We contacted treating physicians and requested they complete a questionnaire on clinical and microbiological data and submit relevant medical records. Two independent observers reviewed materials to confirm that cases met a standardized definition. MAIN OUTCOME MEASURES: Positive culture results, vitrectomy status, microbiology spectrum, and final visual acuity. RESULTS: In total, 615 cases met our case definition. Initial visual acuity was counting fingers or worse for 72%. Among 502 cases with known culture results, 291 (58%) had culture positive results. Twelve percent had positive results for streptococci. More than 99% of cases were treated with intravitreal vancomycin. Vitrectomy was performed in 279 cases (45%), including 201 cases with initial acuity better than light perception. Rates of vitrectomy varied across states, with California having the highest rate and Michigan having the lowest (56% and 19% of cases, respectively). Overall, 43% of individuals achieved visual acuity of 20/40 or better. Poor initial acuity (adjusted odds ratio [OR], 1.08; 95% confidence interval [CI], 1.04–1.12 per 0.10 logarithm of the minimum angle of resolution units), older age at diagnosis (OR, 1.22; 95% CI, 1.03–1.45 per 5-year increase), and more virulent organisms were important predictors of poor final visual acuity. Cases with streptococci infection were 10 times more likely to have poor final acuity than coagulase-negative staphylococci cases (adjusted OR, 11.28; 95% CI, 3.63–35.03). Vitrectomy was not predictive of final visual acuity (adjusted OR, 1.26; 95% CI, 0.78–2.04). CONCLUSIONS: Population-based data on the microbiology of acute postoperative endophthalmitis in the United States after cataract surgery are consistent with prior reports. Vitrectomy usage is higher than that recommended from the Endophthalmitis Vitrectomy Study, with no evidence of increased benefit.